End of Paediatric Posting Assessment of Medical Interns at a Teaching hospital from Coastal Karnataka - Sahana, K.S.; Qadiri, Ghulam Jeelani; Saldanha, Prakash R.M. (Journal of Nepal Paediatric Society, 2019)
Introduction: Internship is very a critical period of a medical undergraduate education during which student evolves into a doctor. The objectives of this study were to assess the interns at the end of their paediatric postings. Materials and Methods. Interns knowledge and skills were assessed at the end of their postings in the must know areas. Assessment was conducted by the trained faculty and interns were given the orientation about it. Method of assessment included OSCE, simulation based using standardized patients and computer-based model driven simulators. Feedback was given to the students immediately at the end of their exam Results: Total 202 interns participated in the exam over the period of two years. New-borns assessment was done more frequently (22.7%) and interpretation of investigations was less frequently assessed (7.9%). Rest of other stations was assessed almost at the equal proportion. Highest score was observed in vaccines section (7.5) and lowest score was seen in procedures assessment (5.5). Conclusion. Interns were found to be weaker in procedural, communication and clinical scenario judgement skills which will help us in planning future training of the Interns.